PERBANDINGAN KEBOCORAN MIKRO PADA RESTORASI KOMPOSIT DENGAN PEMAKAIAN BONDING GENERASI KELIMA DAN BONDING GENERASI KETUJUH - Karina Nabilla; Defriman Djafri; Dedi Sumantri (Faculty of Dentistry Universitas Andalas, 2017)
Composite resin is the most frequently material used for restoring teeth but still failure cases are seen which leading to microleakage. Microleakage might be attributed to various factors, one of them is bonding agent. Various generations of bonding agents have been introduced to overcome the microleakage. The aim of this study was to evaluate the microleakage of composite restorations using the fifth and seventh bonding agent. Class I cavities (3X2X2 mm) were prepared on the occlusal surfaces of 32 human upper premolars. Teeth were classified into two groups according to the type of bonding agent used (n =16). Group I: Fifth Generation of Bonding Agent-Adper Single Bond2. Group II: Seventh Generation of Bonding Agent-Single Bond Universal. All cavities were restored with Filtek Z250 XT composite resin, stored in sterile aquades water at 370C for 24 h. The root apices were sealed with sticky wax, and all the surfaces, except for 2 mm from the margins, were coated with nail varnish. The teeth were immersed in a 1% methylene blue dye solution for 24 h, and then rinsed in running water, blot-dried and sectioned longitudinally through the center of restorations from the buccal to palatal surface. The sections were blindly assessed for microleakage of dye penetration by using a stereomicroscope. Data were collected and statistically analyzed by independent t -test. There was no significant difference (p>0,05) between two groups. The conclusion is fifth generation of bonding agent revealed less leakage compared to the seventh generation even statistically there was no significant difference. Keywords:Microleakage, fifth generation of bonding agent, seventh generation of bonding agent.